Functional properties of liquid whole duck egg - Montuno, Audrey Maybelle Tongco (2007)
The main objective of the study was to evaluate the functional properties of liquid whole duck egg (LWDE) that has been pasteurized (60°C for 3.5 min and 62°C for 40 min) and exposed to 6-continuous-freeze-thaw cycles (-10°C for 72 h0. The pasteurization process adequacy, microbiological, physico-chemical, and functional properties of LWDE were established. The unpasteurized LWDE with a pH of 7.61 was found to be positive for Salmonella spp. Based on the color characteristics (L*= 77.89, a*= 9.88, b*= 30.81, h°= 72.21, C*= 32.35), the unpasteurized LWDE could be characterized as light, yellow-orange with elements of red, yellow, and gray. The functional properties of unpasteurized LWDE were established: 80.0 co viscosity, 40.33 ml of oil/ml of LWDE emulsion capacity, 97.87% stability rating, 2.31% foam overrun, 33.0 min foam stability, and 728.2 g/cm-2 gel strength. Pasteurization protocols at 60° and 62°C were established to be adequate to inactivate salmonella spp. in liquid whole duck eggs (LWDE) using heat resistance parameters of S. enteritidis at D60°C= 0.36 min, D62.8°C=0.06 min, and z=10°F as reference. The established pasteurization lethalities computed (Pc) at 60° and 62°C of 2.86 and 0.77 min were found higher than the pasteurization lethalities desired (Pd) of 2.52 ans 0.42 min, respectively. The pH, emulsion capacity, and foam stability of LWDE significantly decreased (P=0.05) after pasteurization due to denaturation of egg proteins resulting to loss of solubility and aggregation. The viscosity and foam overrun of LWDE significantly increased (P=0.05) due to decrease in solubility and denaturation of ovotransferrin. The color characteristics slightly changed after pasteurization and was attributed to the degradation of carotenoid pigments. Pasteurization did not significantly changed the emulsion stability and gel strength of pasteurized LWDE samples. The 6-continuous-freeze-thaw cycles significantly decreased the pH, viscosity, emulsion capacity and gel strenth of LWDE. These changes were attributed to protein denaturation resulting from ice crystal damage that caused physical and chemical deteriorations in protein molecules. The foam overrun of LWDE and foams produced became resistant to drainage. Aggregation of duck egg was observed after the 3rd freeze-thaw cycle. Changes in foaming properties of LWDE were attributed to protein denaturation of egg proteins and the decrease in pH values of LWDE samples. Based on the color characteristics, the thawed LWDE samples became lighter, less red, less yellow, and less saturated. Changes in color characteristics were attributed to exposure of LWDE to light and oxygen. No significant change was found in the emulsion stabilities of LWDE samples. Pasteurization protocols of 60° - 62°C for 3.5-4.0 min can be recommended for LWDEs. However, i it also recommended that pasteurized LWDE be exposed to a maximum of 3 freeze-thaw cycles as to retain the optimum physico-chemical and functional properties. he foaming properties were established to be the most sensitive functional parameter of LWDE and can be used as an index to assess the overall functional prope